Developing odontoma with an atypical radiological appearance: A case report - Motoko Watanabe; Mamoru Wakoh; Kei Nakajima; Shuji Yoshida; Hitomi Sato; Masahide Koyachi; Kento Odaka; Yuriko Koshimizu; Mika Otonari-Yamamoto; Masayuki Takano; Kenichi Matsuzaka; Akira Katakura; et al. (Oral and Maxillofacial Surgery Cases, 2020)
Developing odontoma, formerly named ameloblastic fibro-odontoma (AFO), shows similar histopathologic appearance to ameloblastic fibroma (AF) in that it is composed of epithelial and mesenchymal elements. However, unlike AF, developing odontoma contains dental hard tissues. Radiologically, developing odontoma shows well-defined, mainly unilocular radiolucency containing various sizes and shapes of radiopaque materials, whereas AF shows well-defined unilocular or multilocular radiolucency without opacities. As such, the definition between developing odontoma and AF is generally clear in intraoral or panoramic radiographs. We present a case of developing odontoma which showed atypical radiological appearance apparently similar to AF. A 9-year-old boy was referred with the chief complaints of delayed eruption of the upper left second deciduous molar and first molar. Panoramic radiography revealed the radiolucent lesion with a well-defined margin and irregular surface. Impacted teeth were involved, but radiopaque materials were not found inside the lesion. Computed tomography showed a multilocular low-density lesion with only a few punctate enamel-like high-density areas. Magnetic resonance imaging showed a heterogeneous internal structure with the same signal intensity as muscle in T1-weighted images and high signal intensity in T2-weighted images with fat suppression. Although these images were atypical, developing odontoma was suspected based on the existence of enamel-like areas. AF was diagnosed by biopsy; however, the histopathological examination revealed dental hard tissues. Subsequently, it was diagnosed as developing odontoma. Recurrence has not been seen in 23 months postoperatively. Further reading of radiographic images over comparison with histopathological specimen was suggested to distinguish between atypical developing odontoma and AF. Keywords: Developing odontoma, Radiological appearance, Ameloblastic fibro-odontoma, Ameloblastic fibroma, Mixed odontogenic tumor